2021
DOI: 10.21037/apm-21-1227
|View full text |Cite
|
Sign up to set email alerts
|

The changes in pyroptosis-related inflammatory factors in the peripheral blood of patients with Henoch-Schonlein purpura

Abstract: Background: Henoch-Schonlein purpura (HSP) is a common capillary allergic bleeding disease. To explore the variation of pyroptosis-related inflammatory factors level in the peripheral blood of patients with HSP.Methods: A total of 87 HSP patients treated in our hospital from June 2020 to March 2021 were selected and divided into the renal impairment group (n=29) and the non-renal impairment group (n=58) according to the presence of hematuria and proteinuria. A total of 50 healthy individuals from the hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have also shown that the treatment regimen of compound glycyrrhizin tablets combined with glucocorticoids can significantly reduce the levels of febrile inflammatory factors in peripheral blood of patients with HSP without renal injury. 23 At the same time, 3 ineffective patients in the treatment group had no renal damage, while three of nine had no improvement in the control group had positive urine protein. Of course, owing to a limited sample size of the present study, it still remains unclear whether it is suggested that Compound Glycyrrhizin can reduce the incidence of renal damage in HSP.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have also shown that the treatment regimen of compound glycyrrhizin tablets combined with glucocorticoids can significantly reduce the levels of febrile inflammatory factors in peripheral blood of patients with HSP without renal injury. 23 At the same time, 3 ineffective patients in the treatment group had no renal damage, while three of nine had no improvement in the control group had positive urine protein. Of course, owing to a limited sample size of the present study, it still remains unclear whether it is suggested that Compound Glycyrrhizin can reduce the incidence of renal damage in HSP.…”
Section: Discussionmentioning
confidence: 92%
“…During the progression of HSPN, IgA deposition may induce apoptosis of human umbilical vein endothelial cells, thereby causing HSP vascular endothelial damage ( 35 ). On the other hand, apoptosis may promote the removal of inflammatory cells, contributing to the control of early inflammatory response and repair self-limiting vasculitis ( 36 ). Hence, there is a complex regulatory link between immune and apoptosis-associated signaling pathways in children with HSPN.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by a recent study that provided evidence that Il-1ß serum levels and the number of peripheral caspase-1-positive cells are increased in IgAV children. After prednisone treatment, Il-1ß and peripheral caspase-1-positive cells remained only elevated in the subgroup of patients who developed nephritis [48]. Pathophysiologically, amongst other functions, IL-1β upregulates the IL-2 receptor, prolongs T-cell survival and has a key role in B-cell proliferation, antibody production and the differentiation of Th17 cells into pro-inflammatory cells [49,50].…”
Section: Predispositionmentioning
confidence: 99%